2019
DOI: 10.22300/1949-8276.11.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Which Way is Up? Orientation and Residential Property Values

Abstract: Builders have long been cognizant of the importance of the siting of a house on a lot, whether to shelter from prevailing weather, allow better access to natural light, gain a scenic view, or more recently for optimal capture of solar energy. Using 2016–2017 sales data for the County of San Diego, we examine the market valuation of house orientation. San Diego provides a good research area as the topography does not lend itself to a grid-like pattern for the street system. Orientation is divided into eight dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the study by (Ma & Narwold, 2019) they suggested that house orientation is a significant factor in determining house valuation. Similarly, (Rashid et al, 2018) studied the orientation of the building found it to be one of the locational factors that affect residential property value.…”
Section: Environmental Factors Sourcementioning
confidence: 99%
“…In the study by (Ma & Narwold, 2019) they suggested that house orientation is a significant factor in determining house valuation. Similarly, (Rashid et al, 2018) studied the orientation of the building found it to be one of the locational factors that affect residential property value.…”
Section: Environmental Factors Sourcementioning
confidence: 99%